Incorporation of Okara into Gluten-Free Cookies with High Quality and Nutritional Value. (11th January 2017) - Ostermann-Porcel, María V.; Quiroga-Panelo, Natalia; Rinaldoni, Ana N.; Campderrós, Mercedes E.
Abstract : Soy products are a source of protein relatively inexpensive and recognized for their high nutritional value and functional properties. Okara is a byproduct from soy milk production. Gluten-free cookies have been developed using okara and commercial manioc flour. Four formulations were developed with different proportions of okara: 50%; 30%; 15%; and 0%. Physicochemical, physical properties, sensory analysis, and nutritional studies were performed. The use of inulin as partial replacement of sugar was evaluated. The incorporation of okara increased protein and fiber content. Furthermore, the hardness of cookies increased while the index of whiteness decreased. From the sensory evaluation, it could be concluded that the cookies presented a great acceptability. The cookies developed in this study have functional characteristics, providing added value to a waste product; furthermore the products were suitable for celiacs with acceptable quality and improved nutrition value.